Test Antifungal Phatogen Extract Secondary Metabolites Of Endophytic Fungi Raru Plant (Cotylelobium melanoxylon) - Uswatun Hasanah; Riwayati Riwayati; Idramsa Idramsa (JBIO: jurnal biosains (the journal of biosciences), 2015)
This study aims to determine the ability of extracts  secondary metabolites of endophytic fungi raru plant Siarang (Cotylelobium melanoxylon) in inhibiting the growth of pathogenic fungi. Pathogenic fungi tested were Collectotrichum, Fusarium oxysporum, Candida albicans and Sclerotium rolfsii. Test antifungal pathogens carried out by using the method of Kirby-Bour, ie by measuring the clear zone located around the paper disc which is the zone of growth inhibition of pathogenic fungi. Measurement of inhibition zone is done by using a caliper or ruler. The results showed that the secondary metabolites of endophytic fungi extracts could inhibit the growth of pathogenic fungus Candida albicans is the clear zone of 10.23 mm. Keywords : endophytic fungus, Cotylelobium melanoxylon, extract of secondary metabolites, fungal pathogens, inhibition zone